"Cyclodiode": results of a standard protocol. Issue 3 (1st March 1999) - Spencer, Anne Fiona; Vernon, Stephen A
Abstract : AIMS: To analyse the results of intraocular pressure (IOP) reduction in refractory glaucoma following diode laser cyclophotocoagulation with a repeatable standard protocol. METHODS: 58 eyes of 53 patients were followed for 6–37 months (mean 19 months) after initial cyclodiode treatment. RESULTS: Mean (SD) pretreatment IOP for the 58 eyes was 33.0 mm Hg (10.7) reducing at final index visit to 16.7 mm Hg (7.8) (p<0.0001). The mean antiglaucoma medication score per eye was significantly reduced from 2.4 (0.8) to 1.4 (1.0) at last index visit (p<0.0001) with 91% of patients able to stop oral acetazolamide. 45% of eyes required more than one treatment and the overall mean per eye was 1.6 (range 1–5). Of eyes with visual acuity 6/60 or better pretreatment, 12 (32%) lost more than two lines of Snellen acuity and two eyes with poorer acuity initially dropped to NPL. Poor visual outcome was associated with the presence of diabetic retinopathy. Hypotony (IOP <5 mm Hg) was noted in two eyes at the last index visit although neither had specific signs of the same. No phthisis was seen. CONCLUSION: The simple treatment protocol, repeated if necessary, appears relatively safe and effective at lowering IOP in eyes with refractory glaucoma.